2020
DOI: 10.5551/jat.52993
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP6 Is Downregulated in Unstable Carotid Atherosclerotic Plaques According to an Integrated Bioinformatics Analysis and Experimental Verification

Abstract: Aims: To investigate the differentially expressed genes (DEGs) and molecular interaction in unstable atherosclerotic carotid plaques. Methods: Gene expression datasets GSE41571, GSE118481, and E-MTAB-2055 were analyzed. Co-regulated DEGs in at least two datasets were analyzed with the enrichment of Gene Ontology Biological Process (GO-BP), Kyoto Encyclopedia of Genes and Genomes (KEGG), protein-protein interaction (PPI) networks, interrelationships between miRNAs/transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
20
0
2
Order By: Relevance
“…Numerous reports found that genetic alteration in critical signaling pathways were significantly associated with glioma tumorigenesis, including EMT, RTK/RAS/PI(3)K, p53 and RB, ERK pathways, and so on [19,20]. IGFBP6 was involved in inhibiting IGF-II actions, promoting cell apoptosis, inducing tumor cell migration, and mediating MAPK, ERK and HIF1A related pathways [9,21,22]. Some research reported that IGFBP6 was correlated with TMZchemoresistance in GBM, and the expression of IGF-1 R and IGF2 in gliomas were associated with shorter overall survival [23].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports found that genetic alteration in critical signaling pathways were significantly associated with glioma tumorigenesis, including EMT, RTK/RAS/PI(3)K, p53 and RB, ERK pathways, and so on [19,20]. IGFBP6 was involved in inhibiting IGF-II actions, promoting cell apoptosis, inducing tumor cell migration, and mediating MAPK, ERK and HIF1A related pathways [9,21,22]. Some research reported that IGFBP6 was correlated with TMZchemoresistance in GBM, and the expression of IGF-1 R and IGF2 in gliomas were associated with shorter overall survival [23].…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Ontology (GO) database, containing three sections: biological progress (BP), cellular component (CC), molecular function (MF), and the Kyoto Encyclopedia of Genes and Genomes (KEGG) database are the most popular tools to learn about gene functions [ 19 ]. Therefore, two databases and the reference value P value < 0.05, which was considered as the significant difference, were used to further study the function of DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…Other datasets were also employed to identify the DEGs. Liu et al (2020) analyzed GSE41571, GSE118481, and E-MTAB-2055 and discovered that JCHAIN, CXCL10, and HMOX1 were the crucial FIGURE 6 | ROC curves for NCF2, IQGAP2, and CD86. (A) The AUC for NCF2 was 0.918.…”
Section: Discussionmentioning
confidence: 99%